Sol-Gel-Processed Metal-Oxide Films for Large-Area Printed High-K Dielectrics - Lee, Won June; Choi, Jun Gyu; Yoon, Myung Han; Park, Sungjun (Metal Oxide-based High-K Dielectrics: Fundamentals and Applications, 2025)
Developing high-performance electronic materials with well-matched electrical, physical, and chemical properties is necessary for advances in the practical electronic applications of large-area flexible electronics, such as displays [1], wearable devices [2, 3], and low-cost disposable circuits [4]. In this regard, various printing techniques [5-8], such as spray, inkjet, screen, flexographic/gravure, and blade/bar methods, have been employed for cost-effective film deposition and fabrication on large-area substrates. Correspondingly, several researchers have widely studied solution-processable electronic materials for their widespread use in device components for versatile electronic applications. Among the device components used in electronics, the dielectric layer plays a vital role as an electrically insulating layer comprising non-conducting materials that are responsive to an externally applied electric field. The dielectric layer provides various functional properties, and these can be categorized and utilized in accordance with the linear/non-linear polarization behaviors presented in response to the specific displacement of dipole moments for functional electronic device applications [9-12], such as thin-film transistors (TFTs), resistive switching memories, energy capacitors, and ferroelectric devices.
Keywords: Dielectric layer; Electronics applications; Electronics materials; K dielectrics; Low-costs; Metal oxide film; Performance; Physical and chemical properties; Sol'gel; Wearable devices